Hubungan Pengetahuan Keluarga dengan Kepatuhan Minum Obat Pasien Skizofrenia di Unit Rawat Jalan Rumah Sakit Jiwa Mutiara Tahun 2023 - Qiyaam, Nurul; Isnaini, Marlinda; Nopitasari, Baiq Leny; Anjani, Baiq lenysia Puspita (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Schizophrenia is a brain disorder that affects thoughts, perceptions, emotions, movements, and behaviors, leading to peculiar and dependent behavior. Patients with schizophrenia may be more likely to adhere to their drug regimens if their families know and support them. This study aims to ascertain how family awareness and medication adherence relate to schizophrenia patients at Mutiara Sukma Mental Hospital's outpatient unit in 2023. The study used a cross-sectional strategy and a correlational research design. It was carried out in March 2023, involved 112 relatives of schizophrenia patients, and was chosen using selective sampling. The results showed that families of patients had good knowledge (38.4%), moderate knowledge (39.3%), and poor knowledge (22.3%). Among the patients, 72.3% were adherent to medication, while 27.7% were non-adherent. The statistical analysis revealed a significant relationship between family knowledge and medication adherence of schizophrenia patients (p=0.000, p<0.05).